2010
DOI: 10.1590/s1516-18462010005000113
|View full text |Cite
|
Sign up to set email alerts
|

Coral amador: efeitos de uma proposta de intervenção fonoaudiológica

Abstract: OBJETIVO: verificar os efeitos de uma proposta de intervenção fonoaudiológica com base na prática educativa, por meio de avaliação de fonoaudiólogos, professores de canto e dos próprios coristas amadores participantes, analisando, em momento pré e pós-intervenção fonoaudiológica, os parâmetros de respiração, projeção e tessitura vocal na voz cantada. MÉTODOS: o programa teve o referencial teórico de ZABALA (1998) sobre a prática educativa. Dez cantores de coral amador responderam a um questionário de caracteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
14
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 15 publications
1
14
0
2
Order By: Relevance
“…Afterwards, other seven articles (8)(9)(10)(11)(12)(13)(14) and two theses (15,16) were excluded as they were not conducted with popular singers, but with choir singers and/or choir conductors. One article was excluded as it deals with a case study with the purpose of reflecting on the mother-baby relationship, by means of body therapy associated to the singing voice production, whose participant had experience with classical music (17) .…”
Section: Resultsmentioning
confidence: 99%
“…Afterwards, other seven articles (8)(9)(10)(11)(12)(13)(14) and two theses (15,16) were excluded as they were not conducted with popular singers, but with choir singers and/or choir conductors. One article was excluded as it deals with a case study with the purpose of reflecting on the mother-baby relationship, by means of body therapy associated to the singing voice production, whose participant had experience with classical music (17) .…”
Section: Resultsmentioning
confidence: 99%
“…The benefit provided by speech therapy has been proven in other studies [22][23][24] in which the singer himself reported improvement in his voice. Speech pathologists, singing teachers but also the choristers themselves perceive positive changes in vocal aspects, as in vocal range, breath and voice projection, after being held these interventions [21][22][23][24] .…”
mentioning
confidence: 82%
“…The benefit provided by speech therapy has been proven in other studies [22][23][24] in which the singer himself reported improvement in his voice. Speech pathologists, singing teachers but also the choristers themselves perceive positive changes in vocal aspects, as in vocal range, breath and voice projection, after being held these interventions [21][22][23][24] . It can be seen that the highest score, with respect to CPIC, was in Defect subscale, followed by the Disability and Handicap; these data are equivalent to the findings of other similar studies 12,17,18,25 , in which the defect and disability subscales had higher scores than the subscale Handicap for all singers.…”
mentioning
confidence: 82%
“…This is the reason why actions by a Speech-Language Pathologist is essential in the control of vocal misuse and abuse in both spoken and singing voices, as the Speech-Language Pathologist, in partnership with the vocal instructor, has subsidies to study and analyze the best techniques for choir singers: respiratory support, coordination between breath and speech, speech articulation, tuning, among other behaviors [18][19][20] . In this context, the evaluation of child and adolescent choir singers provides systematized data about vocal problems, the potentials and limitations that may influence vocal quality, aimed at a good performance and development of the singer 20 .…”
mentioning
confidence: 99%
“…The SpeechLanguage Pathologist may act in choirs, aiming to improve singers' performances and favoring good and effortless vocal emissions. This job, performed by Speech-Language Pathologists alongside vocal instructors is crucial in order to increase the group's capacities and to assure a better sound and artistic result 18 . Therefore, the purpose of this study was to characterize the aspects regarding vocal health, choir singers' knowledge about caring for their own voices, and to conduct an auditory perceptive analysis of the spoken voice, in a child and adolescent choir.…”
mentioning
confidence: 99%